Exploring the molecular and biological mechanisms of host response in chickens infected with highly pathogenic avian influenza virus (H5N1): An integrative transcriptomic analysis - Sare Golpasand; Shahrokh Ghovvati; Zahra Pezeshkian (PLoS ONE, 2025)
The H5N1 strain of highly pathogenic avian influenza (HPAI) has raised worldwide alarm, posing a threat to the health of both animals and humans. The study aimed to identify key genes and biological pathways modulated in chickens infected with H5N1 through meta-analysis. Four microarray datasets from GEO were normalized using RMA, Quantile methods, and the SVA package in RStudio. Differentially expressed genes (DEGs) were screened using the edgR package. Gene enrichment and network analyses were performed, and key genes in the protein-protein interaction (PPI) network were identified using the CytoHubba and MCODE plugins in Cytoscape. Additionally, to investigate the regulatory networks involved, we employed the miRDB web tool to identify microRNAs associated with each hub gene. The resulting miRNA-mRNA interaction network was constructed using Cytoscape software, providing insights into the post-transcriptional regulation of gene expression. Furthermore, WGCNA revealed co-expression modules tied to gene expression profiles. Gene expression analysis identified 259 DEGs between normal and infected lung tissues, with 140 up-regulated and 119 down-regulated genes (adj P-Value<0.05 and |log2 fold change (FC)| > 1). Ten hub genes (EPSTI1, IFIH1, IFIT5, IRF1, IRF7, MX1, OASL, PARP14, RSAD2, USP18) were identified. Up-regulated DEGs activated the host’s innate immune response, highlighting the roles of cytokines and chemokines in inflammation. The study showed that increased expression of interleukins, interferons, and growth factors in the extracellular space is influential for activating innate immunity mechanisms. These findings enhance the understanding of the molecular mechanisms underlying H5N1 infection in chickens.